Revisiting the Code of Muslim Personal Laws: Proposing amendments in an attempt to harmonize with existing state obligations and policies - Kadjim, Mohammad Annesir I. (Animo Repository, 2018)
Under the Code of Muslim Personal Laws, there is a significant difference in the grounds to invoke divorce depending on who will be the one invoking the divorce whether it be the husband or the wife. In accordance with the Islamic tradition of paternal society, men are given less stringent opportunities to divorce as compared to women. In contrast, CEDAW provides that women's rights should be protected by the state, further stating that social and cultural patterns should be modified to eliminate prejudice among sexes. CEDAW even mandated the state parties to ensure equality among men and women before the law including civil matters such as marriage. On the other hand, the Magna Carta for Women, as part of the Philippines' conformance with its obligation to CEDAW, provided for equal rights to women in all matters relating to marriage and family relations. However in another session of the same statute, the state also recognizes the preservation of cultural identity of Moro and indigenous women. There seems to be a conflict here between the said laws and this begs the question as to which law must be upheld. CEDAW defines discrimination against women as "... any distinction, exclusion or restriction made on the basis of sex which has the effect or purpose of impairing or nullifying the recognition, enjoyment or exercise by women, irrespective of their marital status, on a basis of equality of men and women, of human rights and fundamental freedoms in the political, economic, social, cultural, civil or any other field." The fact that there are different methods to be invoked depending on who initiates divorce must raise a red flag already. There exists a clear distinction made as to sex here. Articles 46, 47, 48 and 49 may only be invoked by the husband, while articles 50, 51, 52, and 53 are the only provisions by which the wife may initiate divorce. Section 19 of the Magna Carta for Women provide for rights relating to marriage and family relations. On the other hand, Section 28 of the same law provides for recognition and preservation of cultural identity and integrity. The researcher concludes that a conflict does exist between provisions on divorce under the Code of Muslim Personal Laws with that of the state obligations laid down under CEDAW. Upon careful examination, it is clear and apparent that the divorce provisions under the Code of Muslim Personal Laws are indeed discriminatory to women as discussed in the study. Furthermore, the researcher also concludes that although the enactment of the Magna Carta of Women indeed complements the adherence of the Philippines to CEDAW, but the provisions recognizing and respecting the culture of the minority somewhat create a problem in the implementation of the law.